Systemic sclerosis in Sarawak : a profile of patients trated in the Sarawak General Hospital - Teh, C. L.; Kuan, Yeh Chunn; Wong, J. S. (Springer, 2009)
We performed a cross-sectional study of the demography, clinical and laboratory features of patients with systemic sclerosis patients followed up in our centre from 1984 to 2007. There were 23 cases with the majority of them (96%) being female. They have a mean age of 50.3 years and a mean disease duration of 6.02 (SD 5.82) years. Our patients comprised of multi-ethnic groups with predominantly Chinese (52%), Sarawak natives (35%) and Malays (13%). They have a mean lag time to diagnosis of 24.8 (SD 34.8) months. All the patients have sclerodermatous skin changes with 16(70%) having diffuse scleroderma and 7(30%) having limited scleroderma. The common clinical manifestations found in our patients were Raynaud’s phenomenon (91%), sclerodactyly (65%), digital ulcers (52%) and pulmonary fibrosis (52%). There was low incidence of pulmonary hypertension (13%) and renal involvement (4%). The majority of our patients (67%) have positive ANA with 33% positive Scl-70. The majority received calcium channel blockers (87%), aspirin (48%) and low-dose prednisolone (48%). One patient developed adenocarcinoma of the lung on follow-up. This study demonstrated the rarity of systemic sclerosis in our centre with considerable lag time to diagnosis in our patients. Diffuse cutaneous systemic scleroderma is more common in our centre with rare pulmonary hypertension and renal involvement.